Upregulation of IGF2BP2 Promotes Oral Squamous Cell Carcinoma Progression That Is Related to Cell Proliferation, Metastasis and Tumor-Infiltrating Immune Cells - Zhou, Lijie; Li, Hongyu; Cai, Hongshi; Liu, Wenhui; Pan, Enjiu; Yu, Dongsheng; He, Shuai (Frontiers in Oncology, 2022)
The strong invasive and metastatic abilities of oral squamous cell carcinoma (OSCC) cells in the early stage are the main reason for its poor prognosis. The early diagnosis and treatment of OSCC may reduce the metastasis rate and improve the survival rate. The aim of this study was to explore candidate biomarkers related to the prognosis and progression of OSCC. We performed weighted gene coexpression network analysis to identify key modules and genes associated with OSCC and intersected the differentially expressed genes (DEGs) in The Cancer Genome Atlas (TCGA)-OSCC and GSE30784 datasets. Next, we performed survival analysis and immunohistochemistry to screen and validate the hub gene insulin-like growth factor 2 (IGF2) mRNA binding protein 2 IGF2BP2. We also used TCGA pan-cancer data to verify that IGF2BP2 was expressed at high levels in a variety of cancers and was related to a poor prognosis in patients. Furthermore, we divided patients with OSCC into high and low expression groups based on the median expression level of IGF2BP2. Gene set enrichment analysis (GSEA) showed that IGF2BP2 led to a poor prognosis in OSCC by affecting cancer-related (epithelial-mesenchymal transition, glycolysis, cell cycle, etc.) and immune-related biological functions and pathways. Single-sample GSEA (ssGSEA), CIBERSORT, and xCell algorithms helped reveal that high IGF2BP2 expression was accompanied by a significant reduction in the immune score, stromal score, and microenvironment score and a decrease in the number of infiltrating CD8+ T cells in OSCC. In addition, silencing IGF2BP2 suppressed the proliferation, migration, and invasion of OSCC cells. In general, IGF2BP2 is a potential biomarker for the progression, immunotherapy response, and prognosis of OSCC.